Ageing, Care Need and Long-Term Care Workforce in Germany - Erika Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper aims to show the impact of population ageing on the demand and supply of long-term care workforce. As age is the major driver of the need for care the growth in the number of elderly and oldest old will increase the demand for long-term care services. Since 1995 formal care services in institutions and at home as well as cash benefits for informal home care financed by the long-term care insurance system are available, but only for people with at least substantial impairments in activities of daily living. Thus the bulk of caregiving to the elderly is still the task of the family. In Germany the demand for long-term care workforce will increase significantly. Although also the informal caregiving potential aged 50+ is expected to increase, the increase in the demand for formal care workforce is projected to be higher than the supply. The current shortage of nursing and caring personnel will be strengthened. This requires an expansion of recruitment and retention strategies.
Additional information: This publication was produced as part of the NEUJOBS project, funded by the European Commission through the 7th Framework Programme under contract no. 266833 (http://www.neujobs).; info:eu-repo/grantAgreement/EC/FP7/266833
Keywords: 330; Pflegebedürftigkeit; Pflegeberufe; Gesundheitsberufe; Deutschland